Genome-Wide Identification of Heavy Metal ATPase Family in Aegilops tauschii and Functional Verification of AetHMA4 and AetHMA8 - Xiaolin Liang; Xiaofang Zhang; Yibo Li; Yifan Ding; Hongying Li; Ziyuan Hao; Ning Wang; Xiaojiao Han (Agronomy)
Aegilops tauschii, a monocotyledonous annual grass, recognized as a pivotal progenitor of modern wheat (Triticum aestivum L.), serves as the D-genome donor in hexaploid wheat. This diploid species (2n = 2x = 14, DD) harbors a substantial reservoir of genetic diversity, particularly in terms of biotic and abiotic stress resistance traits. The extensive allelic variation present in its genome has been increasingly utilized for wheat genetic enhancement, particularly through introgression breeding programs aimed at improving yield potential and stress resilience. Heavy metal ATPases (HMAs), which belong to the P-type ATPase superfamily and are also known as P1B-type ATPases, play a crucial role in transporting heavy metals and maintaining metal ion homeostasis in plant cells. HMAs have been extensively studied in model plants like Arabidopsis thaliana and rice. However, this family has not been reported in A. tauschii. Here, we conducted the genome-wide identification and bioinformatics analysis of the AetHMA gene family in A. tauschii, resulting in the discovery of a total of nine AetHMA members. Among AetHMA genes, six pairs are large-block duplication genes, which mainly occur among the four genes of AetHMA2, AetHMA4, AetHMA8, and AetHMA9. Additionally, there is one pair that consists of tandem duplication genes (AetHMA6: AetHMA7). All AetHMAs can be classified into six groups (I–VI), which are further divided into two branches: the copper subclasses and the zinc subclasses. Initially, A. tauschii was grown in a 1/2 Hoagland nutrient solution and subsequently exposed to four heavy metals: zinc (Zn), copper (Cu), manganese (Mn), and cadmium (Cd). Following this treatment, the expression profiles of nine AetHMA genes were assessed. The results indicated that, under zinc and manganese stress, the HMA family members exhibited enhanced expression in the leaves, whereas the expression of most members in the roots was downregulated. In the roots, except for AetHMA2, AetHMA5, and AetHMA8, the expression levels of other members were upregulated in response to Cd exposure. Furthermore, AetHMA4 diminishes the tolerance of yeast to Mn by increasing the absorption of Mn, while AetHMA8 increases the tolerance of yeast to Cd by reducing the absorption of Cd. This study provides experimental data regarding the function of the AetHMA gene in the transport, regulation, and detoxification of heavy metal elements in A. tauschii.